Socio-economic Bonding as an Enabler of Circular Economy Integration in MSMEs: A Community-Based Green Transformation Model for Sustainable Economic Resilience - Fitria Nur Masithoh; Aninda Adistyana Dewi; Uliyatul Mu’awwanah; Miftakhur Rohmah; Mansur (Program Studi Ekonomi Syariah, STAI AN-NAJAH INDONESIA MANDIRI, 2026)
Micro, Small, and Medium Enterprises (MSMEs) in rural contexts face significant barriers to adopting circular economy (CE) practices, yet existing studies focus predominantly on technical and policy dimensions while overlooking socio-relational mechanisms. This study introduces and empirically examines socio-economic bonding—defined as community economic interactions grounded in honesty, mutual respect, trust, and solidarity—as a critical enabler of CE integration among rural MSMEs. Method: A mixed-methods quasi-experimental design with participatory action research was employed, involving 25 MSME actors in Mojokerto, Indonesia, through a three-phase intervention (capacity building, circular innovation, institutional support). Data were collected using pretest-posttest assessments, observations, focus group discussions, and in-depth interviews. Results: Socio-economic bonding significantly facilitated CE adoption, increasing CE literacy by 85% (p<0.001, Cohen's d=3.21), achieving 68% adoption of circular practices, reducing waste generation by 30-40%, and generating additional monthly income of IDR 500,000-1,500,000. Trust in collective action showed the strongest correlation with CE adoption (r=0.71, p<0.001). From an Islamic perspective, socio-economic bonding aligns with 'an taradin (mutual consent), maslahah (public interest), and prohibition of israf (excessive consumption). Implications: The proposed community-based green transformation model offers a replicable framework where socio-economic bonding serves as the transversal mechanism bridging capacity building, innovation, and institutional support for CE adoption in resource-constrained rural settings. Keywords: Socio-economic Bonding; Circular Economy; MSMEs; Green Transformation; Sustainable Economic Resilience.